Description of Geocenamus vietnamensis sp. n. (Nematoda: Merliniidae) from Vietnam - Nguyen, Huu Tien (J Nematol, 2019)
A new species of the genus Geocenamus was isolated from soil and root samples from the rhizosphere of Casuarina equisetifolia (Casuarinaceae) in Quang Nam province, Vietnam. This species is characterized by a round-to-hexagonal labial disc, the presence of a labial region, which is continuous or slightly offset from the body with six sectors, lateral sectors of first labial annulus being smaller than the submedian sectors, the presence of six to seven labial annules; the absence of deirids; stylet length 24 to 28 μm long, body length 776 to 979 μm long; lateral field with six to eight lateral lines, without areolation at mid-body and with areolation in outer bands at the tail region and a pointed tail terminus. Geocenamus vietnamensis n. sp. most closely resembles G. boghiae in having a non-sclerotized head framework and lacking a bursa in the males. It can be clearly distinguished from all other species of the genus Geocenamus by these characteristics. The combination of morphology, morphometric features, and phylogenetic trees, based on D2–D3 of 28S and ITS rDNA sequences, showed that this new species can be clearly separated from all other sequenced species. This record is the first for Geocenamus in Vietnam.